2012
DOI: 10.1021/am3016763
|View full text |Cite
|
Sign up to set email alerts
|

Widely Applicable Coinage Metal Window Electrodes on Flexible Polyester Substrates Applied to Organic Photovoltaics

Abstract: The fabrication, exceptional properties, and application of 8 nm thick Cu, Ag, Au, and Cu/Ag bilayer electrodes on flexible polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) substrates is reported. These electrodes are fabricated using a solvent free process in which the plastic surface is chemically modified with a molecular monolayer of thiol and amine terminated alkylsilanes prior to metal deposition. The resulting electrodes have a sheet resistance of ≤14 Ω sq–1, are exceptionally robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 90 publications
1
32
0
Order By: Relevance
“…We have previously shown that a mixed molecular monolayer of MPTMS and APTMS co‐deposited from the vapour phase is an effective seed layer for the formation of Cu films on both glass and plastic substrates ,. APTMS catalyses the coupling reaction with the substrate, while both APTMS and MPTMS bind strongly to the incoming Cu atoms as they arrive at the substrate resulting in more slab‐like film formation and vastly improved film quality at <10 nm ,,,. Using this approach the surface roughness of a 9 nm evaporated Cu film on glass is reduced from 1.44±0.12 to 1.02±0.05 nm and the initial sheet resistance is reduced from 13.8 to 10.8 Ω sq −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that a mixed molecular monolayer of MPTMS and APTMS co‐deposited from the vapour phase is an effective seed layer for the formation of Cu films on both glass and plastic substrates ,. APTMS catalyses the coupling reaction with the substrate, while both APTMS and MPTMS bind strongly to the incoming Cu atoms as they arrive at the substrate resulting in more slab‐like film formation and vastly improved film quality at <10 nm ,,,. Using this approach the surface roughness of a 9 nm evaporated Cu film on glass is reduced from 1.44±0.12 to 1.02±0.05 nm and the initial sheet resistance is reduced from 13.8 to 10.8 Ω sq −1 .…”
Section: Resultsmentioning
confidence: 99%
“…To enable the formation of uniform slab‐like Cu and Ag films at sub‐10 nm metal thickness a variety of different inorganic and organic nucleation layers have been proposed whose primary function is to suppress metal atom diffusion during early stages of film growth ,,,. For evaporated Cu films the most successful seed layers to date are based on the use of molecular monolayers that chemically bind both to the substrate and Cu, including 3‐mercaptopropyl(trimethoxysilane) [MPTMS] and 3‐aminopropyl(trimethoxysilane) [APTMS] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper films were thermally evaporated onto glass substrates modified with a mixed molecular layer of 3‐mercaptopropyltrimethoxysilane (MPTMS) and 3‐aminopropyltrimethoxysilane (APTMS). We have previously shown that this class of adhesion layer can be applied to both glass and plastic substrates to realize robust copper films without contributing to light absorption . A blend of the immiscible polymers, polystyrene (PS) and poly(methyl) methacrylate (PMMA) in 2‐butanone was spin cast directly onto the copper film (Figure , step 1), whereupon spontaneous phase separation into well‐defined isolated spherical PS domains in a PMMA matrix occurs.…”
Section: Resultsmentioning
confidence: 99%
“…This high cost, along with limited energetic compatibility with frequently used photoactive organic materials, poor flexibility and tendency to crack and/or delaminate, has resulted in a strong interest to find an alternative material for use as the TCE without these disadvantages. Several different materials have been investigated including graphene [5], carbon nanotubes [6], thin metal films [7], metal grids [8], nanowires [9], and conducting polymers [10].…”
Section: Introductionmentioning
confidence: 99%